Influence of humic acid on microbial induced carbonate precipitation for organic soil improvement - Chen, M.; Gowthaman, S.; Nakashima, K.; Kawasaki, S. (Springer Nature, 2022)
Microbial induced carbonate precipitation (MICP) is one of the most commonly researched topics on biocementation, which achieves cementation of soil particles by carbonate from urea hydrolysis catalyzed by microbial urease. Although most MICP studies are limited to stabilizing sandy soils, more researchers are now turning their interest to other weak soils, particularly organic soils. To stabilize organic soils, the influence of humic substances should be investigated since it has been reported to inhibit urease activity and disrupt the formation of calcium carbonate. This study investigates the effect of humic acid (HA), one fraction of humic substances, on MICP. For this purpose, the effects of HA content on CaCO3 precipitation using three strains and on CaCO3 morphology were examined. The results showed that native species in organic soils were less adversely affected by HA addition than the exogenous one. Another interesting finding is that bacteria seem to have strategies to cope with harsh conditions with HA. Observation of CaCO3 morphology revealed that the crystallization process was hindered by HA to some extent, producing lots of fine amorphous precipitates and large aggregated CaCO3. Overall, this study could provide an insightful understanding of possible obstacles when using MICP to stabilize organic soils.
Keywords: Humic acid (HA); Microbial induced carbonate precipitation (MICP); Urease activity; CaCO3 morphology; Soil improvement